2021
DOI: 10.3390/agronomy11081524
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Auxin-Responsive Genes, Phytohormone Profile, and Metabolomic Signature in Leaves of Tomato Cuttings Is Specifically Modulated by Different Protein Hydrolysates

Abstract: Protein hydrolysates (PHs) are employed in agriculture to increase the sustainability of farming systems, with positive results on crop productivity and response against environmental stressors. Nevertheless, the molecular mechanism(s) triggered by their specific activity is not clearly understood. In this work, five PHs obtained by enzymatic hydrolysis of different vegetal protein sources were tested for their root-promoting activity on tomato cuttings. All the treatments improved both root length and number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Samples were ground with mortar and pestle using liquid nitrogen, and the leaves from the same plant were pooled. Then, extraction was performed according to Buffagni et al. (2021) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were ground with mortar and pestle using liquid nitrogen, and the leaves from the same plant were pooled. Then, extraction was performed according to Buffagni et al. (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…Samples were ground with mortar and pestle using liquid nitrogen, and the leaves from the same plant were pooled. Then, extraction was performed according to Buffagni et al (2021). Briefly, 1 g of plant material was extracted in 10 mL of 80% (v/v) methanol acidified with 0.1% formic acid.…”
Section: Untargeted Metabolomic Analysis Of Leavesmentioning
confidence: 99%
“…Transcriptomic (mRNAseq) and proteomic analyses revealed that this positive effect may result from the convergence of several physiological changes related to phytohormones, reactive oxygen species (ROS) scavenging, specific primary and secondary metabolic pathways, transport, and cytoskeletal reorganization [51,61]. In order to evaluate the auxin-like activity, the effects of five plant-derived PHs (Solanaceae-, Malvaceae-, Brassicaceae-, and Fabaceae-derived PHs, and a commercial product resulting from the enzymatic hydrolysis of legume-derived proteins) on the expression of genes involved in auxin signaling (SlIAA2 and SlIAA9) in leaf tissue of tomato plants were compared with distilled water (negative control) and indole-3-acetic acid (positive control) [62]. SlIAA9 was upregulated by four PHs and indole-3-acetic acid, while SlIAA2 was upregulated by the commercial product and the Brassicaceae-derived PH, assuming that these PHs might elicit auxin-like activity to regulate root architecture [62].…”
Section: Root Architecturementioning
confidence: 99%
“…In order to evaluate the auxin-like activity, the effects of five plant-derived PHs (Solanaceae-, Malvaceae-, Brassicaceae-, and Fabaceae-derived PHs, and a commercial product resulting from the enzymatic hydrolysis of legume-derived proteins) on the expression of genes involved in auxin signaling (SlIAA2 and SlIAA9) in leaf tissue of tomato plants were compared with distilled water (negative control) and indole-3-acetic acid (positive control) [62]. SlIAA9 was upregulated by four PHs and indole-3-acetic acid, while SlIAA2 was upregulated by the commercial product and the Brassicaceae-derived PH, assuming that these PHs might elicit auxin-like activity to regulate root architecture [62]. In tomato cuttings, the foliar application of (Malvaceae and Solanaceae) plant-derived PHs positively influenced root length, partially through the interaction between auxins and gibberellins, that both accumulated in response to Solanaceae-and Malvaceae-derived PHs [63].…”
Section: Root Architecturementioning
confidence: 99%
“…Other authors demonstrated the capacity of the tropical-plant extract biostimulant "Auxym®" in mimicking auxin-like effect on sweet cherry fruits due to the presence of peptides and free amino acids which serve as signaling molecules thus suggesting an alternative model for exogenous synthetic hormones application ( Basile et al., 2021 ). Some authors pointed out that biostimulants derived from vegetal origin, induced a modulation of metabolites related to the regulation of the homeostasis of the auxin pool ( Buffagni et al., 2021 ). In addition to protein hydrolysates, several studies reported that many microorganisms, such as strains belonging to the genera Pseudomonas , Bacillus , Pedobacter , Pantoea , Luteibacter , Acinetobacter , Lysobacter , and Enterobacter , have plant growth-promoting properties and capability to produce auxin compounds ( Khan and Doty, 2009 ; Agnolucci et al., 2019 ; Leontidou et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%